Fatty acids profile in meat of Devon young steers, finished in different feeding system - Menezes, Luis Fernando Glasenapp; Restle, João; Kozloski, Gilberto Vilmar; Brondani, Ivan Luiz; Arboitte, Miguelangelo Ziegler; Silveira, Magali Floriano; Nörnberg, José Laerte (Semina: Ciências Agrárias, 2014)
The objective of this study was to evaluate the fatty acid profile of meat of Devon steers finished in feedlot, or winter pasture (pasture of ryegrass - Lolium multiflorum Lam), or tropical pasture (association of millet pasture - Pennisetum americanum (L.) Leeke - and alexander grass - Brachiaria plantaginea). At the beginning of finishing the average weight of steers was 320 kg and the age was 15 months. A completely randomized design with three treatments and variable number of repetitions. The roughage:concentrate ratio from feedlot was 60:40. The lipid content of Longissimus dorsi muscle was influenced by the feeding system, the winter pasture showed higher lipid content in comparison to tropical pasture, while the lipid content of feedlot was intermediary. The tropical pasture showed intramuscular fat more saturated in relation to winter pasture, mainly due to the higher participation of C15:0, C17:0 and C20:0 acids. The feedlot and winter pasture animals showed meat with higher content of monounsaturated fatty acids in relation to tropical pasture, but there was no effect of the diet on the total polyunsaturated fatty acids. The winter pasture provided meat with higher conjugated linoleic acid (CLA) and of omega-3 acids in relation to feedlot, while the tropical pasture did not differ from the other two treatments. Pasture finishing provided omega6/omega3 ratio more benefic in relation to feedlot finishing. The winter pasture finishing provided meat with intramuscular fat more benefic in comparison to feedlot finishing, mainly due to higher CLA content, higher omega-3 acids and lower omega-6/omega3 ratio. Tropical pasture finishing resulted in meat with intermediate nutritional value between winter pasture and feedlot.